Sensitivity and specificity of median nerve ultrasonography in diagnosis of carpal tunnel syndrome - Yazdchi, Mohammad (Dove Medical Press, 2012)
BACKGROUND: Although controversial, recent studies have demonstrated advantages of sonographic techniques in the diagnosis of carpal tunnel syndrome (CTS). The purpose of this study was to assess the utility of median nerve ultrasonography in the diagnosis of CTS in Iranian patients. METHODS: Ninety patents with clinically suspected CTS were studied. Based on gold standard electromyography/nerve conduction velocity studies, wrists with CTS were divided into three groups on the basis of severity of CTS, ie, mild, moderate, and severe. In addition, both sides of the wrist were examined using sonography. Transverse images of the median nerve were obtained and median nerve cross-section areas were measured at three levels, ie, immediately proximal to the carpal tunnel inlet, at the carpal tunnel inlet, and at the carpal tunnel outlet. Furthermore, flexor retinaculum thickness was evaluated. RESULTS: The mean age of the studied patients was 48.52 ± 12.17 years. Median values of the median nerve cross-section at the carpal tunnel inlet, carpal tunnel outlet, and proximal carpal tunnel significantly differed between the wrists with and without CTS (P < 0.05). Comparisons between the CTS groups (mild, moderate, and severe) and non-CTS wrists demonstrated that the median cross-sections of median nerve at the carpal tunnel inlet, carpal tunnel outlet, and inlet proximal carpal tunnel were significantly greater in the severe CTS group than in the other three groups (P < 0.05). The results showed that the median nerve cross-section at the three levels of carpal tunnel could only fairly differentiate severe CTS from other cases. CONCLUSION: The present study demonstrated that median nerve ultrasonography cannot replace the gold standard test (nerve conduction velocity) for the diagnosis of CTS because of low overall sensitivity and specificity, although it might provide useful information in some patients.